The Criminal Law Policy on the General Election System in Indonesia - Lubis, Mhd Teguh Syuhada; Saragih, Rayani; Hanifah, Ida; Koto, Ismail; Jacob, John Tumba (Faculty of Law, Universitas Jenderal Soedirman, 2023)
General elections are a crucial pillar of democracy in Indonesia, allowing citizen participation in selecting leaders and shaping policies. Strong criminal law policies are necessary to preserve the integrity of elections, despite challenges in consistent law enforcement and clear definitions of election violations. The aim of this research is to assess the implementation and effectiveness of criminal law policies in preventing and addressing election violations in Indonesia and to identify their impact on the election process. The research findings indicate that the implementation of criminal law policies in preventing and addressing election violations is crucial. This is achieved through stringent election regulations, strict enforcement of criminal sanctions, careful monitoring and investigation, and swift handling of violations. The effectiveness of criminal law policies is also evident in deterring violations, ensuring transparency in funding, and active citizen participation in monitoring. Criminal law policies have a significant impact on the election process. Positive impacts include efforts to prevent election crimes, protect voting rights, and address election law violations through strict regulations. Prevention of election crimes such as spreading false information and the use of violence is tightly regulated to maintain election integrity. Protecting voters' rights is a focal point, with prohibitions against bribery and intimidation practices. However, the negative impact lies in the potential misuse of criminal law for political purposes, which can undermine the principles of presumption of innocence and human rights.